2021
DOI: 10.3390/jcm10143076
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes between Stand-Alone Zero-Profile Spacers and Cervical Plate with Cage Fixation for Anterior Cervical Discectomy and Fusion: A Retrospective Analysis of 166 Patients

Abstract: Stand-alone (SA) zero-profile implants are an alternative to cervical plating (CP) in anterior cervical discectomy and fusion (ACDF). In this study, we investigate differences in surgical outcomes between SA and CP in ACDF. We conducted a retrospective analysis of 166 patients with myelopathy and/or radiculopathy who had ACDF with SA or CP from Jan 2013–Dec 2016. We measured surgical outcomes including Bazaz dysphagia score at 3 months, Nurick grade at last follow-up, and length of hospital stay. 166 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…[77][78][79] Including a cervical plate decreases the risk of graft extrusion. 80 Ossification of the posterior longitudinal ligament is an indication of an anterior cervical corpectomy with fusion. An anterior cervical corpectomy and fusion consists of discectomies, followed by the formation of a corpectomy trough, followed by a corpectomy.…”
Section: Authors' Preferred Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…[77][78][79] Including a cervical plate decreases the risk of graft extrusion. 80 Ossification of the posterior longitudinal ligament is an indication of an anterior cervical corpectomy with fusion. An anterior cervical corpectomy and fusion consists of discectomies, followed by the formation of a corpectomy trough, followed by a corpectomy.…”
Section: Authors' Preferred Treatmentmentioning
confidence: 99%
“…Complications of the anterior approach include esophageal injury, vertebral artery injury, airway compromise, and a high risk of pseudarthrosis 77–79 . Including a cervical plate decreases the risk of graft extrusion 80 . Ossification of the posterior longitudinal ligament is an indication of an anterior cervical corpectomy with fusion.…”
Section: Authors’ Preferred Treatmentmentioning
confidence: 99%
“…As a result, anchored stand-alone spacers were developed for use in ACDF ( Fig. 1 ) cohorts ( Son et al, 2014 ; Sommaruga et al, 2021 ).
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…Appropriate selection of surgical intervention is based on patient characteristics, disease pathology, and risk factors. Sommaruga et al [ 11 ] compared the surgical outcomes including Bazaz dysphagia score, Nurick grade, and hospital stay between stand-alone zero-profile implants and more traditionally used cervical plating in anterior cervical discectomy and fusion. The study, consisting of 116 patients, found a shorter hospital course and operation time for stand-alone implants; however, neurologic and dysphagia outcomes were similar across both groups.…”
mentioning
confidence: 99%